Narrating belief in China: a comparison of the school curriculum and students’ perceptions - Zhao, Zhenzhou (Journal of beliefs and values, 2021)
Chinese people’s beliefs have greatly diversified in the reform era even though teaching the dominant Marxist ideology in schools has continued to be compulsory. However, little is known about how the state has interpreted and taught ‘belief’ in the school curriculum and how students construe the meanings of belief in their daily lives. Through analysing the civics curriculum and textbooks and conducting interviews with first-year university students, this study collected macro and micro narratives that reveal a dynamic interaction between the party-state and individual students that informs how belief is interpreted and practised in contemporary China. The findings suggest that the state has imposed a hierarchical elite-oriented belief structure in the curriculum narratives, in which the dominant political beliefs are represented as public, ultimate beliefs for all members of society and only elite individuals are able to become Marxism believers. Non-elite students are instead encouraged to develop their own beliefs but to subject their private beliefs to political (public) beliefs. The informants’ perceptions of their schooling experiences suggest inclinations towards the privatisation and de-politicisation of beliefs. The findings of this study provide new insights into the understanding of belief in China’s schooling system.